Families, alliances, clientage and urban space: the case of the late medieval Genoese alberghi (thirteenth-fifteenth centuries) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
Within the multifarious context of communal Italy, the Genoese aristocratic alberghi, known thanks to the studies of Edoardo Grendi, Ennio Poleggi and Luciano Grossi Bianchi, and Jacques Heers, stand out as a peculiar example that enables to observe the relationship between aristocracy and urban space throughout the late Middle Ages. The Genoese case is peculiar not only because of its originality, already emphasised by past literature, but also in view of the presence of extremely rich documentary sources. In a city characterised by multiple and overlapping territorial divisions (compagne, conestagie, contrate), it is thus possible to follow the evolution of these aristocratic confederacies (involving around 200 families of different sizes) from the early communal period. Grendi had emphasised the ‘demotopographic’ character of the alberghi which express a principle of organisation of the urban space based on a common cognomen. The paper aims at reconsidering the relationship between the power of the late medieval aristocratic alberghi and urban territory by focusing not only on strategies for maintaining control of their residential buildings, but also aspects of social interaction.
Keywords: Thirteenth-fifteenth centuries; late Middle Ages; Genoa; urban history; territoriality; alliances